Co-Ni supported yttrium oxide material as a catalyst for ammonia decomposition to COx-free hydrogen. (19th March 2023) - Li, Honghai; Guo, Lexin; Qu, Jianing; Fang, Xianxin; Fu, Yaqian; Duan, Jihai; Wang, Weiwen; Li, Chaojie
Abstract: The preparation of CO2 -free hydrogen by decomposing ammonia using non-precious metal catalysts has received widespread attention. Co-based catalysts have good catalytic activity and low synthesis costs. Therefore, we prepared a series of Y2 O3 -loaded Co and Co–Ni bimetallic catalysts by the co-precipitation method. The structure-activity relationship of the catalysts during NH3 decomposition was investigated by X-ray diffraction, N2 adsorption-desorption, transmission electron microscopy, and Temperature-programmed reduction by hydrogen. The ammonia decomposition performance of the bimetallic Co–Ni was examined to elucidate the effect of the relative amount of the active metal of the catalyst on the catalytic activity and compared it with the monometallic Co/Y2 O3 . Among the tested catalysts, 20Co–10Ni/Y2 O3 showed the best catalytic performance as well as good stability. The ammonia decomposition rate of the 20Co–10Ni/Y2 O3 catalyst was 85.02% at 550 °C and GHSV of 9000 mL h −1 ·gcat −1, which was 28.5% higher than that of the 20Co/Y2 O3 catalyst. The high activity of 20Co–10Ni/Y2 O3 catalyst was attributed to the uniform loading of Co and Ni, high specific surface area, and a large number of mesopores. At the same time, Co and Ni exhibited synergistic effects to produce suitable adsorption energy of nitrogen atoms, which further enhanced the catalytic activity of the catalyst. Graphical abstract: Image 1 Highlights: Bimetallic catalysts offer better catalytic properties than monometallic catalysts. The ammonia decomposition rate of 20Co–10Ni/Y2 O3 was 85.02% at 550 °C. The mesoporous Co–Ni/Y2 O3 has a high specific surface area and metal dispersion. The catalysts have the benefits of simple synthesis, good stability and low price.